The consumption pattern of goat meat in Ilorin metropolis of Kwara State, Nigeria (2011)
Goat is a multi-purpose animal whose uses range from consumption, companionship to commercial meat production. Its production and consequent consumption is widely accepted in Nigeria among the different ethno-religious sects unlike pig, dog and donkey. The paper examined the factors that affect consumption pattern of both kid and mature goat meat in Ilorin metropolis of Kwara State, Nigeria. Primary data were collected from 150 consumers of goat meat through the use of structured questionnaires. The data were analyzed using descriptive statistics and multinomial logit model. The study results showed that 10% of the respondents in the study area consumed both kid and mature goat meat, while the remaining 20% and 70% consumed the kid goat only and mature goat meat only categories, respectively. Tenderness and unpalatable nature of the kid goat meat were found to reduce its demand. The results obtained also showed that the number of the dependants of consumers significantly influenced consumers' preference for the goat meat consumed. The likelihood ratio for the model, lambda (A) is 16.9 which is significant at 5% level. This implies that the goat meat consumer groups are heterogeneous. The multinomial logistic estimate for the combined goat meat consumer groups revealed that income and number of dependants of respondents were significant and therefore explained why individuals prefer to consume either the combination of kid and mature goat meat or the mature goat meat instead of the kid goat. The educational status of respondents and price of other meat products were not significant and therefore did not significantly influence individual's preference for a combination of kid and mature goat meat or only mature goat meat, instead of consuming the kid type of meat only. The study therefore recommends that efforts should be "lade to create awareness of the dangers of consuming meat with high cholesterol content which has been linked to cause many diseases coupled with training of butchers and goat meat processors on modern methods of processing cholesterol-free meat for healthy consumption.